Vegetation dynamics and climate variability over the past 2000 years inferred from Son Kul marsh in the western Tianshan Mountains - Zhang, Dong-liang; Li, Yao-ming; Li, Kai-hui; Ma, Xue-xi; Yang, Yun-peng (Journal of mountain science, 2021)
A pollen study was conducted on an alpine marsh sediment in the Son Kul Basin and was allowed to reconstruct changes in vegetation dynamics and climatic information in the western Tianshan Mountains during the past 2000 years. Pollen diagram reveals that regional vegetation is dominated by alpine meadow in the past 2000 years, being similar with modern vegetation components in the basin. The Artemisia /Chenopodiaceae-indicated moisture exhibits a warm-dry Roman Warm Period (RWP, ∼0–∼500 AD), a cold-dry Dark Ages Cold Period (DACP, ∼500–∼800 AD), a warm-wet Medieval Warm Period (MWP, ∼800–∼1350 AD), a cold-dry Little Ice Age (LIA, ∼1350–∼1850 AD) and a warm-dry Current Warm Period (CWP, since ∼1850 AD). Our pollen-based moisture reconstructions are supported by other nearby moisture records. Combined with other pollen data in the western Tianshan Mountains, we found that the vegetation was relatively stable before ∼1650–∼1750 AD and the anthropogenic activities obviously intensified afterwards (especially at the middle-elevation sites). Further work involving more and higher-resolution palaeovegetation records would contribute to fully understand the information on the complex links between environmental, climatic and anthropogenic changes in the western Tianshan Mountains.